Depth distribution of soil, glyphosate, and aminomethylphosphonic acid (AMPA) properties and analysis of crop yield in six long-term experiments - Aparicio, Virginia Carolina; De Geronimo, Eduardo; Frolla, Franco Daniel; Domínguez, Germán; Galarza, Carlos Martin; Barbagelata, Pedro Anibal; Irizar, Alicia Beatriz; Costa, José Luis; Cerda, Artemio (Springer, 2023)
Context: Argentina is the third-largest user of pesticides per year, with more than 65% of the herbicide being glyphosate. Glyphosate and aminomethylphosphonic acid (AMPA) have similar properties in terms of environmental behavior and toxicity. Scientific evidence of the presence of glyphosate and AMPA in the environment has revealed the vulnerability of the current production system. No-till is used in 90% of agricultural land in Argentina and is deeply associated with the use of glyphosate for weed control on genetically modified organisms. Objective: The purpose of our research is to determine the vertical distribution of some soil properties, glyphosate and AMPA content, crop yield response to tillage, and glyphosate use efficiency (GUE) for two contrasting tillage systems: no-tillage (NT) and conventional tillage (CT) in Argentina. Methods: In winter/spring 2015, three undisturbed soil sub-samples were collected from the top 20 cm of depth in 6 field experiments with a minimum duration of 15 years and mollic epipedon. Analytical determination of glyphosate and AMPA were determined through ultra-high performance chromatography coupled with a tandem mass spectrometer (UHPLCMS/MS). In each field experiment, crop yield from the 2011/2012 season to the 2015/2016 season, and the kg of glyphosate active ingredient (a.i) used per ha−1 were recorded. Both data were used for estimating GUE, expressed in Mg grain kg−1 a.i. Differences in soil properties, glyphosate, and AMPA concentration were compared using a PROC MIXED model. Results and conclusions: Soil properties and glyphosate-AMPA concentration showed a stratification from 0 to 20 cm depth, but only organic matter (OM) and AMPA differed by tillage in some field experiments at 0–2 and 2–5 cm depth. Sixty percent of crop yields and 69.4% of GUE did not present statistically significant differences between tillage systems. In the present study, the GUE has a general mean of 1.2 Mg grain per kg of a.i ha−1 year−1. We report here the translocation of minerals within the A horizon of soils with molic epipedon. On the other hand, our results indicate that the molic epipedon can accumulate AMPA. Our results show that glyphosate accumulates in the soil due to its recurrent application and regardless of the soil management carried out. Significance: The GUE concept is novel and may result in an easy-to-understand tool for farmers to reduce herbicide abuse. Agriculture is not sustainable if the current use of pesticides is maintained, despite having soils of high natural fertility, high organic carbon content, and a favorable climate for grain production.